The paleoclimatic record from a 345 m long ice core from the Hans Tausen Iskappe - Hammer, Claus Uffe; Johnsen, S. J.; Clausen, Henrik B.; Dahl-Jensen, Dorthe; Gundestrup, Niels; Steffensen, Jørgen Peder (Meddelelser om Grønland. Geoscience, 2001)
The 345 m long ice core retrieved from the Hans Tausen Ice Cap in 1995 (82,5°N, 38°W) in Western Peary Land was sampled in situ for later paleoclimatic δ18Omeasurements in Copenhagen. The upper 125 m covers a little more than 1000 years and indicates strong persistent warming from the late 1920-ties, a maximum warming in the early 1960-ties and a variable climate with no particular trend since the 1960-ties. The δ record over the past 100 years shows similarities with the temperature records from the Greenland west coast stations, Iceland, and the Faroe Islands. The 20th century is the warmest in the entire record, while the periode 1700-1900 A.D. is the coldest during the past 2000 years. A maximum of warm climate seems to be reached around 900-1100 A.D. which then declines to the colder conditions around 1700 A.D. The climatic interpretation of the deepest 105 m of the δ record is more complicated due to the non-steady state of the ice cap: The implication for the paleoclimatic interpretation will be discussed. No glacial ice is present in the bottom ice.